Feminist Theological Themes in the Biblical Art of Lilian Broca: From Lilith to Mary Magdalene - Beavis, Mary Ann (Feminist theology, 2024)
For three decades, the Canadian artist Lilian Broca has been creating art featuring biblical women: Lilith/Eve, Esther, Judith and Mary Magdalene. These are not single artworks, but series, presenting these women in the contexts of their narratives. In contrast with traditional artistic representations of these figures, dominated by the male gaze, Broca brings a feminist lens to their stories. Broca’s work not only converges with feminist theology and biblical studies, but she also uses this scholarship as part of her research, pointing to a fruitful and significant relationship between feminist art and academic theology.